Reassessing the feasibility of adopting dollarization in Latin America - León Padilla (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - This paper analyses the possibility of Latin America's (LA) major economies adopting dollarization, considering that in the last decade macroeconomic instability has once again challenged the ability of certain economies to properly manage their own currency. Design/methodology/approach To determine the feasibility of adopting the US dollar as official currency, the author uses the framework of optimum currency area (OCA) theory, since, in fact, dollarization is an incomplete monetary union. The author uses a structural vector autoregressive (SVAR) model to identify what type of structural shock - country-specific, regional or global - prevails in LA economies. For this purpose, the US output is used to represent the global output and determine how the shocks of the US influence the output trajectory of each LA nation. The higher the influence of the US product, the lower the costs of adopting the US dollar. Findings The results of the variance decomposition show that the influence of the US shocks in the gross domestic product (GDP) trajectory of LA countries has significantly decreased over the last two decades, even in the currently dollarized economies. The estimates for Venezuela and Argentina show that the importance of US shocks in the trajectory of their GDP is low. Therefore, the cost of adopting the US dollar as the official currency would be high. Originality/value In view of hyperinflation and macroeconomic imbalances in certain LA nations, the dollarization debate has resurfaced in recent years. However, the literature that empirically evaluates the feasibility of adopting dollarization as a monetary system under current economic conditions is limited.
Keywords: E42; E52; F33; F36; F4; F44; 330; Argentina; Dollarization; Latin America; Monetary unions; SVAR; Venezuela